On contact CR-submanifolds of sasakian manifolds - Koji Matsumoto (International Journal of Mathematics and Mathematical Sciences)
Recently, K.Yano and M.Kon [5] have introduced the notion of a contact CR-submanifold of a Sasakian manifold which is closely similar to the one of a CR-submanifold of a Kaehlerian manifold defined by A. Bejancu [1].